Analysis of Factors Affecting the Stock Price of the Company PT Indofood Tbk for the period 2012 - 2023 - , Nirmalasari; Hou, Amin (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the factors that affect the share price of the company PT Indofood Tbk for the period 2012 - 2023. This study uses a type of quantitative research is a research method in which it uses a lot of numbers. The population in this study is the financial statements of PT Indofood Sukses Makmur Tbk in 2012 - 2022 which are listed on the Indonesia Stock Exchange (IDX) which have been published. The samples in this study are ROE, ROA, NPM, DAR and the company's stock price. Data analysis was performed using multiple regression analysis. Classical assumption test and hypothesis testing. Data analysis was tested using SPS Version 25 software. The results of this study are as follows: 1) Return On Asset (ROA) which has a significant positive effect on stock prices, 2) Return On Equity (ROE) which has a significant positive effect on stock prices, 3) net profit margin (NPM) which has a significant positive effect on stock prices, 4) debt to asset ratio (DAR) has no significant positive effect on stock prices and simultaneously ROA, ROE, NPM and DAR variables have a positive and significant effect on stock prices at PT. Indofood Sukses Makmur Tbk.